Access to functionalized 3-amino-benzothiophenes using keteniminium intermediates. Issue 47 (25th November 2015) - Lumbroso, Alexandre; Behra, Julien; Kolleth, Amandine; Dakas, Pierre-Yves; Karadeniz, Ulfet; Catak, Saron; Sulzer-Mossé, Sarah; De Mesmaeker, Alain
Graphical abstract: Abstract: We describe a very efficient access to 3-aminobenzothiophenes using substituted phenylthioacetamides via a 6π-electrocylization of the corresponding keteniminium intermediates. The ease of this electrocyclization allows the use of N -allyl and N -diallyl protecting groups leading to the corresponding primary or secondary amines after mild deprotection.